2007
DOI: 10.1016/j.chembiol.2007.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of In Vivo Potency and Selectivity of Epoxysuccinyl-Based Inhibitors of Papain-Family Cysteine Proteases

Abstract: The papain-family cathepsins are cysteine proteases that are emerging as promising therapeutic targets for a number of human disease conditions ranging from osteoporosis to cancer. Relatively few selective inhibitors for this family exist, and the in vivo selectivity of most existing compounds is unclear. We present here the synthesis of focused libraries of epoxysuccinyl-based inhibitors and their screening in crude tissue extracts. We identified a number of potent inhibitors that display selectivity for endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…4). The treatment of U-937 Mfs with CtsBspecific CA-074 [32], CtsX-specific AMS-36, CtsB-, and CtsXspecific AMS-30 [33] inhibitors and the CtsS-specific inhibitor LHVS [34] strongly attenuated the extracellular degradation of DQ-collagen IV. Notably, this process was not affected by the broad-spectrum MMP inhibitor Batimastat, suggesting that MMPs are not crucial for extracellular collagenolytic activity during 3D invasion of human Mfs.…”
Section: Ecm Degradation Of Human Mfs Is Mediated By Cysteine Cathepsinsmentioning
confidence: 99%
“…4). The treatment of U-937 Mfs with CtsBspecific CA-074 [32], CtsX-specific AMS-36, CtsB-, and CtsXspecific AMS-30 [33] inhibitors and the CtsS-specific inhibitor LHVS [34] strongly attenuated the extracellular degradation of DQ-collagen IV. Notably, this process was not affected by the broad-spectrum MMP inhibitor Batimastat, suggesting that MMPs are not crucial for extracellular collagenolytic activity during 3D invasion of human Mfs.…”
Section: Ecm Degradation Of Human Mfs Is Mediated By Cysteine Cathepsinsmentioning
confidence: 99%
“…The cathepsin-specific ABP DCG-04 has been applied to the evaluation of cathepsin inhibitors in RIP1-TAG2 transgenic mice, a mouse model of pancreatic cancer [42,43]. In these studies, inhibitors were injected into mice, and normal and tumor tissue samples were collected and analyzed for residual cathepsin activity.…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%
“…Importantly, fluorescently-labeled DCG-04 enabled the biochemical identification and monitoring of the cysteine cathepsins during tumorigenesis in these mice. In a follow-up study, a panel of cathepsin inhibitors was evaluated in these mice using radiolabeled DCG-04 [42]. Inhibitors were optimized for selectivity and potency based on these results and then were reprofiled in vivo.…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%
“…Previously Watanabe et al reported the synthesis of a R 1 derivative with oxygen atom substitutes as an inhibitor of epoxysuccinyl-peptide cathepsin B inhibitor, 13) Sadaghiani et al also synthesized a similar epoxysuccinyl-peptide cathepsin B inhibitor with a phenyl group at the R 1 position. 9) Both molecules however failed to maintain the overall inhibition and selectivity to Cathepsin B. Here we successfully synthesized a series of E64d derivatives with Methionine (Met, contains sulfur) substitute at R 1 position.…”
mentioning
confidence: 99%
“…1). 9) Both are derivatives of the epoxysuccinyl-peptide and readily bind to the S 1 ′-S 2 ′ subsites of cathepsin B as highly selective inhibitors. 10,11) The selectivity of E64d and its related analogs has been determined to be due to efficient hydrogen-bond interactions between a free carboxylic acid on the inhibitor and two histidine residues in the occluding loop structure found in cathepsin B.…”
mentioning
confidence: 99%